PENGARUH FIRM SIZE, SALES GROWTH DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR TRANSPORTASI YANG TERDAFTAR DI BEI PERIODE 2019-2023 - Lestari, Dini Martinda; Afriani, Raden Irna; Suwaroh, Suwaroh (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
Tax is a sector that plays an important role in the economy, tax avoidance is one of the company's actions in avoiding taxes, one of the factors that can influence tax avoidance is firm size, sales growth and leverage. This research aims to determine the influence of firm size, sales growth and leverage on tax avoidance in transportation sector companies listed on the IDX for the 2019-2023 period, either partially or simultaneously. The research method used is descriptive quantitative, using a purposive sampling technique with a population of 12 companies while the sample is 9 companies with a 5-year observation period so that the total data is 45 data processed with SPSS Version 26. The results of testing the first hypothesis (H1) significance value = 0.001 < 0.05 and tcount = 2.327 with ttable = 2.01 then Ha is accepted H0 is rejected (H2) significance value = 0.032 < 0.05 and tcount = 2.327 with ttable = 2.01 then Ha is accepted H0 is rejected (H3) significance value = 0.003 < 0.05 and tcount = 2.456 with ttable = 2.01 then Ha is accepted H0 is rejected (H4) significance value is 0.007 < 0.05 or sig < 0 .05 and the value of Fcount>Ftable or Fcount = 4.679 and Ftable = 2.60 then Ha is accepted H0 is rejected. The conclusion of this research shows that (H1) there is an influence between firm size on tax avoidance (H2) there is an influence between sales growth on tax avoidance (H3) there is an influence between leverage on tax avoidance (H4) firm size, sales growth and leverage simultaneously influence against tax avoidance